Association between job satisfaction and workers' quality of life in a public maternity hospital in the far north of Brazil - Marques-Duarte,Manuela Siraiama (2019)
Abstract Objectives: to correlate the levels of job satisfaction (JS) and quality of life (QOL) of public maternity workers. Methods: quantitative and correlational cross-sectional study. Sample composed of 199 state public servants, of both genders, of different age groups and professions, working at the Women's Hospital Mother Luzia (WHML), in Macapá (AP). Three questionnaires were used: Sociodemographic, Job Satisfaction S20/23 and WHOQOL-Brief. Statistical analysis was performed by Pearson correlation and analysis of variance, with statistical significance at 5%. Results: most of the sample consisted of women (84.2%), aged between 30 and 39 years (40.7%), with a partner (64.3%), practicing physical activity (50.8%). With university education, (61.8%), income up to four minimum wages (53.3%), worked in two or more jobs (53.7%); and weekly workload of up to 30 hours (79.4%). They reported job dissatisfaction (75.4%). The average overall QOL was 65.62 (± 12.45). JS was associated with QOL (p<0.001) and number of jobs (p = 0.019). QOL was associated with male gender (p= 0.022), income (p= 0.004), ST (p <0.001), physical activity (p= 0.067) and workload (p= 0.011). The correlations between JS and QOL were all significant. Conclusions: the quality of life of WHML workers was directly and progressively associated with job satisfaction, which meant that higher levels of job satisfaction favored the quality of life.